MD5 in a web-based population data management application to improve account security - Nistrina, Khilda; Rustiyana, Rustiyana; Rosmalina, Rosmalina; Sri Rahayu, Nenden; Puja Permana, Ridwan (Institute of Computer Science (IOCS), 2024)
This research focused on designing and implementing a population data management information system by applying the MD5 algorithm as account security. The population data management information system itself is an information system to make it easier to manage population data to find out and make reports on the number of village residents, as well as make it easier to make certificates. The research case study was carried out at the Jatisari village office, there were several obstacles in the ongoing population data management process in Jatisari village, namely that the management of population data was still in the form of physical files which were vulnerable to damage and loss, and this way of management created the problem of difficulty in finding population information. In addition, information systems are vulnerable to hacking, so a process is needed to verify who can obtain population data or information. Therefore, the aim of this research was to create a population data management application (SIDAKEP) that can simplify the process of managing population data, by implementing the Message-Digest 5 (MD5) algorithm as account security to protect the system from irresponsible parties. By using a qualitative method approach and the SDLC Waterfall development model in application design. The results of this research were the population data management application can help the Jatisari village office government, especially the Head of the Government Section, make population data management easier, more effective and efficient